2018
DOI: 10.1038/s41598-017-18397-5
|View full text |Cite
|
Sign up to set email alerts
|

Primed primary metabolism in systemic leaves: a functional systems analysis

Abstract: Plants evolved mechanisms to counteract bacterial infection by preparing yet uninfected systemic tissues for an enhanced defense response, so-called systemic acquired resistance or priming responses. Primed leaves express a wide range of genes that enhance the defense response once an infection takes place. While hormone-driven defense signalling and defensive metabolites have been well studied, less focus has been set on the reorganization of primary metabolism in systemic leaves. Since primary metabolism pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 63 publications
6
51
0
Order By: Relevance
“…In the process of pathogen infection a series of genes and pathways are activated, and extensive efforts have been devoted to understanding plant defense signaling pathways (Uppalapati et al ., ). Emerging evidence has shown a causal link between primary metabolism and defense responses to plant pathogens (Bolton, ; Rojas et al ., ; Lecompte et al ., ; Schwachtje et al ., ). In the present study, MTC was demonstrated to be extensively involved in R. solanacearum –tomato interactions.…”
Section: Discussionmentioning
confidence: 97%
“…In the process of pathogen infection a series of genes and pathways are activated, and extensive efforts have been devoted to understanding plant defense signaling pathways (Uppalapati et al ., ). Emerging evidence has shown a causal link between primary metabolism and defense responses to plant pathogens (Bolton, ; Rojas et al ., ; Lecompte et al ., ; Schwachtje et al ., ). In the present study, MTC was demonstrated to be extensively involved in R. solanacearum –tomato interactions.…”
Section: Discussionmentioning
confidence: 97%
“…They respond to "pathogen associated molecular patterns" (PAMPs) by activating a PAMPtriggered immunity (PTI) or an effector-triggered immunity (ETI) mediated by receptors able to specifically recognize pathogens (Boller and He, 2009;Navarova et al, 2012). The consequence can be the establishment of a "systemic acquired resistance" (SAR) status, which may increase resistance in the whole plant to subsequent attacks (Navarova et al, 2012;Shah et al, 2014;Schwachtje et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some of the metabolic responses to St. maltophilia and S. plymuthica volatiles, namely glucose reduction, increase in malate and fumarate, the above‐mentioned decrease in putrescine and the transient reduction in glutamate, are reminiscent of Pseudomonas ‐primed primary metabolism in systemic leaves of A. thaliana (Schwachtje et al . ), but the relevance of this similarity and the role of volatiles in priming systemic responses remain to be investigated.…”
Section: Resultsmentioning
confidence: 99%